1998
DOI: 10.1177/104063879801000205
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Pathogenicity of Adenoviruses and Reoviruses Isolated from Broiler Chickens in Alabama

Abstract: Abstract. Adenoviruses and reoviruses isolated from commercial broiler chickens were evaluated for gastrointestinal pathogenicity in specific-pathogen-free Leghorn chickens. The viruses were originally isolated from either the proventriculus or a gastrointestinal pool of tissues of broiler chickens with proventriculitis or enteritis. Isolates were cloned by terminal dilution. Day-old chickens were inoculated by oral and ocular routes with undiluted tissue culture fluids (titers of 10 2 -10 4 TCID 50 /ml) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 19 publications
2
15
0
2
Order By: Relevance
“…It has been reported that two strains of FAV cause gizzard erosion and necrotizing pancreatitis without hepatic or intestinal lesions when FAV is administered experimentally by oral inoculation. 12 The observed pancreatic lesions were clearly different from the lesions of malabsorption syndrome (runting and stunting syndrome) such as atrophy, occlusion of the pancreatic ducts, interstitial fibrosis, and dilation of the acinar lumens. 13,23 Inclusions in the epithelial cells of the biliary passages were observed in four chickens in trial 1.…”
Section: Discussionmentioning
confidence: 82%
“…It has been reported that two strains of FAV cause gizzard erosion and necrotizing pancreatitis without hepatic or intestinal lesions when FAV is administered experimentally by oral inoculation. 12 The observed pancreatic lesions were clearly different from the lesions of malabsorption syndrome (runting and stunting syndrome) such as atrophy, occlusion of the pancreatic ducts, interstitial fibrosis, and dilation of the acinar lumens. 13,23 Inclusions in the epithelial cells of the biliary passages were observed in four chickens in trial 1.…”
Section: Discussionmentioning
confidence: 82%
“…Some FAVs that had originally been isolated from either the proventriculus or a gastrointestinal pool of the tissues of broiler chickens caused gizzard erosions by experimental infection. 22 In our previous studies, outbreaks of adenoviral gizzard erosion (AGE) in slaughtered broiler chickens in Japan were examined, and an FAV serotype-1 named FAV-99ZH was isolated from the gizzard lesions with adenoviral intranuclear inclusion bodies; 31 also, AGE was experimentally reproduced in chickens inoculated with FAV-99ZH. 28 However, only a small number of specific-pathogen-free (SPF) white leghorn chickens were used, and no immunohistochemical examination was done during the experimental infection.…”
mentioning
confidence: 99%
“…Apesar do ARV não ter sido detectado nestes tecidos, não exclui sua atividade em uma fase inicial da infecção, que poderia de alguma forma contribuir para o agravamento das lesões causadas pelo MS (Rosenberger & Olson 1997). A presença de inϐiltrado inϐlamatório mononuclear no proventrículo, caracterizando um quadro de proventriculite, possivelmente está associado à via de inoculação (via oral) do ARV (Rosenberger & Olson 1997, Lenz et al 1998. Inϐiltrado linfohistiocitário intenso principalmente no espaço porta e presença de heteróϐilos foi observado no ϐí-gado, além de pontos de necrose hepática focal em 43,75% (7/16) dos frangos.…”
Section: Resultsunclassified